Mapping the insomnia patient journey in Europe and Canada - O’Regan, David; Garcia-Borreguero, Diego; Gloggner, Fenna; Wild, Imane; Leontiou, Chrysoula; Ferini-Strambi, Luigi (Frontiers in Public Health, 2023)
Introduction: Insomnia affects daily functioning and overall health, and is thus associated with significant individual, societal, and economic burden. The experience of patients living with insomnia, their perception of the condition, and its impact on their quality of life is not well documented. The objective of this study was to map the patient journey in insomnia and identify unmet needs.Participants were individuals with insomnia, and healthcare professionals (HCPs) who treat insomnia, in the United Kingdom, France, Germany, Italy, and Canada. Qualitative interviews (50 patients, 70 HCPs) and a quantitative survey (700 patients, 723 HCPs) were conducted to inform the patient-journey mapping and obtain information on the emotions, perceptions, and experiences of patients and HCPs.The patient journey comprises seven phases. The first defines the onset of insomnia symptoms. Phase 2 represents self-initiated behavior change to improve sleep (e.g., sleep hygiene, reducing caffeine, exercise). The next phase is characterized by use of over-the-counter (OTC) treatments, which generally fail to provide lasting relief. Phase 4 describes the first HCP consultation (occurring several months to several years after onset) and typically occurs at a crisis point for the patient; patients may be looking for an immediate solution (e.g., medication), which may not align with their HCP's recommendation. The following stage comprises sleep hygiene/behavioral changes (± OTC treatment) under HCP guidance for many patients, although offering prescription treatments without a sleep hygiene stage under supervision is more common in some countries. Phase 6 describes prescription medication initiation, where patients fluctuate between relief/hopefulness and a sense of failure, while HCPs try to balance the need to provide relief for the patient while maintaining best medical practice and minimizing adverse effects. The final phase (living with long-This is a provisional file, not the final typeset article term insomnia) represents an indefinite period during which sleep issues remain unresolved for many patients, with most of them continuing to use prescription treatments for longer than indicated and creating their own variable, self-managed regimens combining multiple modalities.Conclusions: This patient journey analysis for insomnia revealed seven distinct phases, highlighting different touchpoints where insomnia management could be optimized.